The Need Analysis for Developing Microbiology Practical Program in the Topic of Heavy Metals Bioremediation Microorganisms - Amelia, Trisna; Liliasari; Kusnadi; Aditiawati, Pingkan (Postgraduate, University of Mataram, 2023)
The involvement of bacteria in lowering the concentrations of heavy metal contaminants in the environment is one of the most recent topics of discussion in the field of microbiology. This topic hasn't been brought up much in microbiology lectures thus far in the classroom. Therefore, it is important to analyze the requirement for the construction of a microbiology practical model with the focus on investigating heavy metal-bioremediating bacteria as environmental polluting agents. The curriculum papers in the biology education study program were analyzed using quantitative and descriptive research methodologies, with a focus on the microbiology course. Additionally, this study used both closed- and open-ended questions. We studied a total of 45 fourth-semester microbiology students from four different institutions, six microbiology lecturers from several Indonesian universities, and four biology teachers from Tanjung Pinang. It was discovered that environmental bioremediation needs to be covered in more detail in microbiology lectures and practicum for aspiring biology teachers based on an analysis of the curriculum, students' perspectives, and instructors' perceptions. Lectures on the subject of heavy metal bioremediation should cover it in detail and should provide useful knowledge. The teacher believes that lab exercises have the potential to be a successful teaching method for this subject.